Analisis Strategi Pemasaran di Toko Najwa Dalam Menciptakan Kepuasan Pelanggan - Larasati, Suci; Kadri, Moh (Fakultas Ekonomi dan Bisnis Islam _ IAIN Sultan Amai Gorontalo, 2021)
This study aims to determine the Marketing Strategy at Najwa Store in creating customer satisfaction. This type of research is descriptive quantitative, the total sample of 15 customers with a sampling technique that census. The data collection method is direct observation, interviews and by using a questionnaire. The results of this study indicate that in creating customer satisfaction at Najwa Store it is important to know the importance of the marketing mix that is the set of variables used by Najwa Stores to increase consumer satisfaction (buyers), wherein the variables of the marketing mix consists of seven variables: price, product completeness, promotion of goods, location, service quality, product quality, and facilities.